Towards Environmental Restoration and Sustainability: Embracing the African Ubuntu Philosophy - Khomba, James Kamwachale Khomba (Strathmore Law Journal, 2025)
Cultural beliefs and philosophies are foundational and fundamental in shaping a society and its natural environment. Lately, there have been various discussions about the values of the African Ubuntu philosophy in many aspects as it relates to issues of environmental degradation and restoration, human relationships, business ethics and corporate governance. As a governing philosophy, Ubuntu is inclusive in nature as it considers all members of society as one entity aiming at achieving one purpose. Within the same context, this paper discusses the importance of cultural beliefs and philosophies in shaping society and the natural environment, with a focus on the African Ubuntu philosophy. The paper aims to explore how Ubuntu's principles can offer insights for mitigating environmental degradation, achieving ecological balance, and ensuring a sustainable future. It highlights that while legal frameworks like the Plastics Treaty are essential, cultural norms and beliefs rooted in African heritage can play a crucial role in environmental restoration. The paper argues that in addition to formal legal instruments, non-formal norms, customs, ethics, and beliefs that are deeply rooted in African cultures can play a crucial role in environmental restoration and sustainability. It explores how the Ubuntu philosophy, which emphasizes interconnectedness among people, nature, and the cosmos, can inform efforts to mitigate environmental degradation and promote ecological balance. The paper aims to inspire a global dialogue on how Ubuntu philosophy can transcend geographical and cultural boundaries to address the plastic pollution crisis and foster a sustainable future for our generations to come.